Электронный учебник по современным средствам автоматизации решения математических задач - Пересыпкин, А. Н.; Свидерская, Л. И. (УАДО, 2004)
Structure of the electronic textbook includes the description of such known software as MathCad, Mathematica and MatLab. The electronic textbook can be realized both in a local network, and on the personal computer. In case of use of the textbook in a local network on сервере the program - environment ensuring support of all computer textbook is placed. The electronic textbook contains test system and has a set of the individual tasks.